Sensing abilities of functionalized calix[4]arene coated QCM sensors towards volatile organic compounds in aqueous media - Temel, Farabi; Ozcelik, Egemen; Türe, Ayşe Gül; Tabakci, Mustafa (Elsevier Science Bv, 2017)
This study presents the sensing studies of QCM sensors which coated with calix[4]arene derivatives bearing different functional groups towards some selected Volatile Organic Compounds (VOCs). Initial experiments revealed that QCM sensor coated with calix-3 bearing bromopropyl functionalities was relatively more effective sensor for methylene chloride (MC) emissions than the other calix[4]arene coated QCM sensors, in aqueous media. In further experiments, this effective calix-3 coated QCM sensor were used in detailed sensing studies of selected VOCs. However, the results demonstrated that calix-3 coated QCM sensor was most useful sensor for toluene (TOL) emissions among all. Moreover, the sensing of TOLs with calix-3 coated QCM sensor was also evaluated in terms of sorption phenomena. Consequently, calix-3 coated QCM sensor was good sensor for TOL emissions, and thus it demonstrated that the coating of QCM sensor surface with calixarenes was good approach for sensing of the VOCs. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Calix[4]arene; Quartz crystal microbalance; Sensor; Sensing; Volatile organic compounds; Coating